Comparative genomics of Mycobacterium avium subsp. hominissuis strains within a group of captive lowland tapirs - Hanka Brangsch; Sandra Marcordes; Anne Busch; Michael Weber; Silver A. Wolf; Torsten Semmler; Dirk Höper; Sten Calvelage; Jörg Linde; Stefanie A. Barth (PLoS ONE, 2025)
Within a group of three captive lowland tapirs (Tapirus terrestris) suffering from clinically apparent mycobacteriosis, non-tuberculous Mycobacterium avium subsp. hominissuis (MAH) strains were isolated from the animals and the tapir’s enclosure. Based on MIRU-VNTR findings, which identified two closely related INMV profiles (124 and 246), a micro-evolutionary event was assumed, and four available MAH strains were submitted to whole genome sequencing (short- and long-read technologies). Surprisingly, the differences based on single nucleotide polymorphisms (SNPs) were exceptionally high between the four strains, i.e., between 841 and 11,166 bases, due to a strong impact of homologous recombination. Thus, an ad hoc core genome multilocus sequence typing (cgMLST) scheme was created and pangenome analysis was conducted for determining the genomic similarity between the strains. The INMV246 isolate obtained from sputum on the enclosure floor and one INMV124 isolate of tapir #2 showed the highest congruence, suggesting that both originated from a shared source. The other two INMV124 isolates were genomically distinct from these strains. Nevertheless, in all four strains two plasmids were detected, which were highly conserved between the strains. The study showed that the genomic variability between MAH strains isolated from the same site within a short period of time can be exceptionally high and the influence of homologous recombination needs to be considered when determining MAH strain relationships, particularly via SNP analyses.